PENGEMBANGAN MODUL DIGITAL BERBASIS PROJECT BASED LEARNING UNTUK MENGOPTIMALKAN MINAT BELAJAR DAN KREATIVITAS SISWA SEKOLAH DASAR - Teguh Adi Irawan; Bambang Subali; Tri Suminar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effectiveness of Project-Based Digital Modules to optimize student interest and creativity in elementary school science lessons. Using R&D research and development methods. By using the ADDIE method. The research subjects were fourth grade elementary school students. This research uses a questionnaire instrument to obtain the necessary data. Questionnaire instrument to determine the quality of the Digital Module being developed. Based on analysis of research data, it was found that the Digital Module can increase students' interest in learning and creativity in grade IV elementary school science and science lessons, because this Digital Module is a valid, practical and effective teaching material for students by being designed to be more interesting and not boring. From the results of the research that has been carried out, it can be concluded that the results of the development of the Project-Based Digital Module are declared valid. Data obtained from validation from several experts, namely media experts at 91.54%, material experts at 94.67%, and language experts at 96.43%, with an average of 94.21% including the very valid category. The results of the development of this Digital Module were stated to be practical from the data from the calculation of the small group test student questionnaire (Small Group) at 95.20% in the very feasible category. The results of the development of the Project-Based Digital Module were declared effective from data obtained through large group testing with an average N-Gain of 0.91%, including the high category.